Influence of complex disorder on skew-scattering Hall effects in L1(0)-ordered FePt alloy - Zimmermann, Bernd; Long, Nguyen H.; Mavropoulos, Phivos; Blügel, Stefan; Mokrousov, Yuriy (PHYSICAL REVIEW B, 2016)
We show by first-principles calculations that the skew-scattering anomalous Hall and spin Hall angles of L1(0)-ordered FePt drastically depend on different types of disorder. A different sign of the anomalous Hall angle is obtained when slightly deviating from the stoichiometric ratio towards the Fe-rich side as compared to the Pt-rich side. For stoichiometric samples, short-range ordering of defects has a profound effect on the Hall angles and can change them by a factor of 2 as compared to the case of uncorrelated disorder. This might explain the vast range of anomalous Hall angles measured in experiments, which undergo different preparation procedures and thus might differ in their crystallographic quality.